877. North American Phase 3/3b Experience with Long-Acting Cabotegravir and Rilpivirine: Efficacy, Safety, and Virologic Outcomes. (4th December 2021) - Taiwo, Babafemi O; Tan, Darrell; Patel, Parul; Teichner, Paula; Polli, Joseph; Garside, Louise; D'Amico, Ronald; Talarico, Christine L; Van Solingen-Ristea, Rodica; Baugh, Bryan; Spreen, William; Aboud, Michael; et al.
Abstract: Background: Cabotegravir (CAB) plus rilpivirine (RPV) is the first complete long-acting (LA) regimen recommended by treatment guidelines for the maintenance of HIV-1 virologic suppression. CAB+RPV LA dosed every 4 weeks (Q4W) or every 8 weeks (Q8W) demonstrated noninferior efficacy in multinational Phase 3/3b trials. This post hoc descriptive analysis summarizes efficacy, virologic outcomes, safety, and treatment preference for US and Canadian (CAN) participants through Week (W) 48. Methods: This analysis focuses on data for US/CAN participants naive to CAB+RPV (n=376) from the larger pooled population of the ATLAS, FLAIR, and ATLAS-2M Phase 3/3b studies (N=1245). Endpoints included the proportion of participants with plasma HIV-1 RNA ≥ 50 and < 50 c/mL at W48 (FDA Snapshot algorithm), incidence of confirmed virologic failure (CVF; 2 consecutive HIV-1 RNA ≥ 200 c/mL), safety, and treatment preference through W48. Results: 376 US/CAN participants received CAB+RPV LA Q4W or Q8W. Median (range) age was 39y (20–74); 14.9% were female, 66.0% were White. At W48, 93.1% (350/376) maintained virologic suppression (HIV-1 RNA < 50 c/mL), 1.9% (7/376) had HIV-1 RNA ≥ 50 c/mL, and 0.8% (3/376) met the CVF criterion, consistent with the overall global pooled population (Table 1). Two of the three participants with CVF had ≥ 2 of the three baseline factors (archived RPV resistance-associated mutations [RAMs], HIV subtype A6/A1, body mass index [BMI] ≥ 30 kg/m 2 ) previously associated with CVF. Among the US/CAN participants with a single baseline factor, none met CVF. Overall, archived RPV RAMs were observed in 3.2% (12/376), HIV subtype A6/A1 in 1.1% (4/376), and BMI ≥ 30 kg/m 2 in 26.3% (99/376) of participants. Safety and injection site reaction findings were similar to the overall pooled population (Table 2). Most participants (120/134, 89.6%) preferred LA over oral dosing (7/134, 5.2%). Table 1. Snapshot outcomes following CAB+RPV LA Q4W and Q8W at Week 48 in participants naive to CAB+RPV from ATLAS, FLAIR, and ATLAS-2M (ITT-E population) Table 2. Safety summary through Week 48 following CAB+RPV LA Q4W and Q8W or comparator ART in participants naive to CAB+RPV from ATLAS, FLAIR, and ATLAS-2M Conclusion: In US/CAN Phase 3/3b trial participants, CAB+RPV LA was highly effective and well tolerated, with outcomes consistent with the overall pooled population. Baseline prevalence of archived RPV RAMs and subtype A6/A1 was low and aligned with regional prevalence/surveillance data. CAB+RPV LA provides a tolerable and effective injectable LA treatment option for virologically suppressed US/CAN individuals with HIV. Disclosures: Babafemi O. Taiwo, MBBS, Gilead (Consultant)Merck (Consultant)ViiV Healthcare (Consultant) Darrell Tan, MD PhD, Abbvie (Grant/Research Support)Gilead (Grant/Research Support)GlaxoSmithKline (Scientific Research Study Investigator)ViiV Healthcare (Grant/Research Support) Parul Patel, PharmD, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Paula Teichner, PharmD, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Joseph Polli, PhD, FAAPS, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Louise Garside, PhD, GlaxoSmithKline (Employee) Ronald D'Amico, DO, MSc, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Christine L. Talarico, M.S., GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Rodica Van Solingen-Ristea, MD, Janssen Research and Development (Employee)ViiV Healthcare (Employee) Bryan Baugh, MD, Janssen, Johnson & Johnson (Employee, Shareholder) William Spreen, PharmD, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Michael Aboud, MBChB, MRCP, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Matthew Bosse, DO, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee)